PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) DALAM PEMBELAJARAN GERAK DASAR LARI CEPAT DENGAN MENGGUNAKAN PERMAINAN SIRKUIT FORMULA 1 (STUDI PADA SISWA KELAS V SDN KLOPOSEPULUH I SUKODONO) - YAKUSNI, (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The game Formula 1 Circuit is a positive exercise in which the arena likes a formula 1 racing car can be the attraction of students to carry out these activities, so as to enhance physical fitness, can ultimately improve sprint technique. Based on the results of this study can be stated that the implementation of cooperative learning model think pair share (TPS) in the game of Formula 1 Circuit is very effective in helping students to improve the technical ability of sprint. The application of this learning model can be used as an alternative to learning that can still be developed on the subject of further study. Keywords: cooperative learning, think pair share, F1 circuit game